Early Childhood Mental Health Promotion through Faith-Based CBT Approaches: A Systematic Review and Future Directions - Hayatul Mala; Asna asna; Ahmad Hafidz Lubis (Universitas Al-Falah As-Sunniyah Kencong Jember, 2026)
This systematic review examines the application of faith-based or religiously sensitive Cognitive Behavioral Therapy approaches in promoting early childhood mental health. It addresses the gap in culturally and spiritually contextualized mental health interventions for young children, particularly within faith-based educational settings. The review synthesizes existing literature to evaluate the effectiveness of integrating faith elements into CBT for children, highlighting potential benefits, challenges, and future research directions. This paper opens a global discourse for faith-sensitive approaches in children’s mental health and offers new directions for CBT to be more culturally and spiritually contextual within faith-based environments.